Rapid and Sequential Dual Oxime Ligation Enables De Novo Formation of Functional Synthetic Membranes from Water‐Soluble Precursors. (2nd June 2022) - Flores, Judith; Brea, Roberto J.; Lamas, Alejandro; Fracassi, Alessandro; Salvador‐Castell, Marta; Xu, Cong; Baiz, Carlos R.; Sinha, Sunil K.; Devaraj, Neal K.
Abstract: Cell membranes define the boundaries of life and primarily consist of phospholipids. Living organisms assemble phospholipids by enzymatically coupling two hydrophobic tails to a soluble polar head group. Previous studies have taken advantage of micellar assembly to couple single‐chain precursors, forming non‐canonical phospholipids. However, biomimetic nonenzymatic coupling of two alkyl tails to a polar head‐group remains challenging, likely due to the sluggish reaction kinetics of the initial coupling step. Here we demonstrate rapid de novo formation of biomimetic liposomes in water using dual oxime bond formation between two alkyl chains and a phosphocholine head group. Membranes can be generated from non‐amphiphilic, water‐soluble precursors at physiological conditions using micromolar concentrations of precursors. We demonstrate that functional membrane proteins can be reconstituted into synthetic oxime liposomes from bacterial extracts in the absence of detergent‐like molecules. Abstract : Dual oxime bond formation enables the spontaneous generation of functional membranes from non‐amphiphilic, water‐soluble precursors at physiological conditions in the micromolar concentration range. In situ lipid synthesis proceeds in the absence of detergents, facilitating membrane protein reconstitution.